2020
DOI: 10.2147/cmar.s259424
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosomal Circ-ZNF652 Promotes Cell Proliferation, Migration, Invasion and Glycolysis in Hepatocellular Carcinoma via miR-29a-3p/GUCD1 Axis</p>

Abstract: Background: Circular RNAs (circRNAs) play a crucial role in hepatocellular carcinoma (HCC) progression. However, the role of exosomal circRNAs in HCC is still largely unknown. We aimed to explore the function of exosomal circ-ZNF652 in HCC. Methods: The morphology and size of exosomes were examined by transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA). The expression of circ-ZNF652, ZNF652 mRNA, microRNA-29a-3p (miR-29a-3p) and guanylyl cyclase domain containing 1 (GUCD1) mRNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Further validation approach confirmed that miR-29a directly targets SIRT1 to inhibit the proliferation and cell cycle progression of HCC [ 56 ]. Li et al showed that overexpression of miR-29a suppressed glycolytic phenotype to impede proliferation, migration, and invasion of HCC by targeting guanylyl cyclase domain containing 1 (GUCD1) [ 57 ]. In addition, the role of circRNA circ-ZNF652 in positively regulating miR-29a expression levels in HCC tumorigenicity was revealed [ 57 ].…”
Section: Mir-29a Acts To Counteract Metabolic Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further validation approach confirmed that miR-29a directly targets SIRT1 to inhibit the proliferation and cell cycle progression of HCC [ 56 ]. Li et al showed that overexpression of miR-29a suppressed glycolytic phenotype to impede proliferation, migration, and invasion of HCC by targeting guanylyl cyclase domain containing 1 (GUCD1) [ 57 ]. In addition, the role of circRNA circ-ZNF652 in positively regulating miR-29a expression levels in HCC tumorigenicity was revealed [ 57 ].…”
Section: Mir-29a Acts To Counteract Metabolic Adaptationmentioning
confidence: 99%
“…Li et al showed that overexpression of miR-29a suppressed glycolytic phenotype to impede proliferation, migration, and invasion of HCC by targeting guanylyl cyclase domain containing 1 (GUCD1) [ 57 ]. In addition, the role of circRNA circ-ZNF652 in positively regulating miR-29a expression levels in HCC tumorigenicity was revealed [ 57 ]. More recently, Song et al demonstrated that miR-29a exerts HCC-counteracting effect by suppressing oncogene roundabout homolog 1 (Robo1) with direct binding at post-transcriptional level [ 58 ].…”
Section: Mir-29a Acts To Counteract Metabolic Adaptationmentioning
confidence: 99%
“…Further examination on the exosome-enriched fraction (30–150 nm) showed that the levels of LINC00161 were upregulated in patients with HCC in contrast to controls ( p < 0.05). No statistical significance was detected for the expression of LINC00161 in HCC urine and serum exosome-free samples compared with controls [ 99 ]. Previously, LINC00161 was shown to be expressed significantly higher in HCC tissues and its high expression was related to a poor prognosis [ 119 ].…”
Section: Exosomal-derived Lncrnas and Circrnasmentioning
confidence: 99%
“…Despite the work from Li [ 99 ] being focused on the identification of the molecular effects derived from the transfer of exosomal circ-ZNF652 in cancer recipient cells, where the miR-29a-3p sponging promoted proliferation, migration, invasion, and glycolysis by affecting the guanylyl cyclase domain containing 1 (GUCD1) expression, it provided also evidence of circ-ZNF652 being higher in exosomes collected from cancer patients, compared to controls [ 99 ]. However, this evidence was derived from the analysis of 33 HCC samples and no further investigation of its diagnostic or prognostic potential was conducted.…”
Section: Exosomal-derived Lncrnas and Circrnasmentioning
confidence: 99%
“…The expression of circRNA_100338 is positively correlated with poorer of OS and PFS of HCC patients ( Huang et al, 2017 ). circ_0005075 promotes HCC progression via miR-431 ( Li et al, 2018 ), and exosomal circ-ZNF652 could transfer to HCC cells to promote cell proliferation, migration, invasion, and glycolysis in HCC via the miR-29a-3p/GUCD1 axis ( Li Y. et al, 2020 ). CircMAST1 elicits HCC progression by sponging miRNA-1299 and stabilizing CTNND1.…”
Section: The Role Of Circrnas In Human Hepatocellular Carcinomamentioning
confidence: 99%